2014
DOI: 10.1002/2014gl059269
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure beneath SE Tibet from joint analysis of receiver functions and Rayleigh wave dispersion

Abstract: New constraints on the pattern of crustal flow in SE Tibet are obtained from joint analysis of receiver functions and Rayleigh wave dispersion with a newly deployed seismic array. The crust in the Sichuan-Yunnan Diamond Block has an average thickness of~45 km and gradually thins toward the Indo-China Block to the west and the Yangtze Block to the east. High V P /V S ratios are detected to the west of the Xiaojiang fault, but not in the Yangtze Block to the east. The S wave velocity profile reveals that intra-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 43 publications
8
48
0
Order By: Relevance
“…7) throughout the mid-crust in most of Tibet has also been observed in a number of previous studies (e.g. Cotte et al 1999;Rapine et al 2003;Caldwell et al 2009;Guo et al 2009;Li et al 2009;Yang et al 2012;Agius & Lebedev 2014;Jiang et al 2014;Li et al 2014;Sun et al 2014;Bao et al 2015;Deng et al 2015;Gilligan et al 2015). Our results have high resolution across the entire Tibetan Plateau and the Pamirs, whereas many previous studies have mainly focused on more restricted geographical regions.…”
Section: P O S S I B L E C Au S E O F T H E L O W V E L O C I T Y L Asupporting
confidence: 85%
“…7) throughout the mid-crust in most of Tibet has also been observed in a number of previous studies (e.g. Cotte et al 1999;Rapine et al 2003;Caldwell et al 2009;Guo et al 2009;Li et al 2009;Yang et al 2012;Agius & Lebedev 2014;Jiang et al 2014;Li et al 2014;Sun et al 2014;Bao et al 2015;Deng et al 2015;Gilligan et al 2015). Our results have high resolution across the entire Tibetan Plateau and the Pamirs, whereas many previous studies have mainly focused on more restricted geographical regions.…”
Section: P O S S I B L E C Au S E O F T H E L O W V E L O C I T Y L Asupporting
confidence: 85%
“…The mechanically weak midlower crust has also been supported by several lines of evidence from geophysical observations, such as intra-crustal LVZs (Bao et al, 2013;Ceylan et al, 2012;Fu et al, 2010;Li et al, 2008;Xu et al, 2013a;Xu and Song, 2010;Yang et al, 2012;Yao et al, 2008), low electrical resistivity in the mid-lower crust (Bai et al, 2010;Unsworth et al, 2005;Wei et al, 2001), high V p /V s ratios (Sun et al, 2014;Xu et al, 2007), high heat flow (Hu et al, 2000), and strong attenuation (Bao et al, 2011a;Zhao et al, 2013), indicating the existence of partial melt and viscosity reduction in the mid-lower crust and thus the possibility of crustal flow. In addition, strong positive radial anisotropy with faster horizontally polarized shear wave further suggests sub-horizontal alignment of mica and/or amphiboles in the crust due to ductile flow beneath SE Tibet (Huang et al, 2010;Shapiro et al, 2004;Xie et al, 2013).…”
Section: Implications For the Deformation Of Se Tibetmentioning
confidence: 70%
“…Recent studies suggest that there may exist two channels of crustal flow in SE Tibet (Bai et al, 2010;Sun et al, 2014;Zhao et al, 2013). On the basis of magnetotelluric images, Bai et al (2010) observed two channels of high conductivity at depths of 20-40 km in east Tibet, which they interpreted as distinct channels of crustal flow.…”
Section: Implications For the Deformation Of Se Tibetmentioning
confidence: 99%
See 1 more Smart Citation
“…The P wave tomography conducted by Lei and Zhao found that broad high-V anomalies are visible from the Burma arc northward in the mantle transition zone (MTZ) beneath eastern Tibet, which is also the case in several other studies [45][46][47], and it has been inferred that they may represent the eastward subduction of the Indian slab along the Burmese arc. That our high-D anomalies are at a depth of 400-500 km (the depth of the MTZ) provides additional evidence for eastward subduction.…”
Section: Discussionmentioning
confidence: 67%